Studi Penggunaan LPG Dari Aktivitas Rumah Tangga Di Wilayah Pengembangan II Dan Wilayah Pengembangan III Kota Pekanbaru - Praja, Silvany Mutiara; Sasmita, Aryo; Asmura, Jecky (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The purpose of this study was to find out the use of LPG household fuels in WP II dan WP III Pekanbaru city. Random sampling method. total sample is 267 families. this study uses descriptive analysis that contains secondary data, study of literature, and primary data. WP II and WP III Pekanbaru City that use LPG fuel respectively at 99% and 98%. While the rest uses fuel other than LPG in WP II, which is 1% and WP III is 2%.Keywords: Use of household LPG, LPG, and Household